Study of HDPE/PET/E-GMA blends: toughening, rigidity, and thermal and morphology behavior (2024)
The purpose of this study was to utilize E-GMA as a compatibilizer to enhance the mechanical properties of recycled blends of high-density polyethylene, polyethylene terephthalate, and ethylene-glycidyl methacrylate copolymer (HDPE/PET/E-GMA), with the aim of manufacturing plastic soda crates. The results showed that toughness increased without losing rigidity. Flexural strength improved by 11% and impact strength by 8% when the PET content was 20%, indicating that E-GMA acts as a compatibilizer. These results can be applied to improve the mechanical properties of recycled materials in an upcycling context.